2018
DOI: 10.1093/gbe/evy148
|View full text |Cite
|
Sign up to set email alerts
|

Gene-by-gene or localized dosage compensation on the neo-X chromosome in Drosophila miranda

Abstract: Many organisms have a global mechanism for dosage compensation (DC) operating along the entire male X chromosome, which equalizes gene expression on the male X with that on the two Xs in females and/or on autosomes. At the initial stage of sex chromosome evolution, however, gene-by-gene (or localized) DC may also be necessary because the degeneration of Y-linked genes occurs independently at different times. We therefore tested whether the up-regulation of X-linked genes depends on the status of their Y-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 30 publications
8
24
1
Order By: Relevance
“…Such findings support the idea that many of the patterns seen in sex chromosomes are representative of supergenes in general. Indeed, rapid evolution of dosage compensation similarly occurred in the 10 million-year-old sex chromosomes of the plant Silene latifolia ( Muyle et al, 2012 ) and in two Drosophila species neo-sex chromosomes that are only a few million years old ( Nozawa et al, 2014 ; Alekseyenko et al, 2013 ; Nozawa et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings support the idea that many of the patterns seen in sex chromosomes are representative of supergenes in general. Indeed, rapid evolution of dosage compensation similarly occurred in the 10 million-year-old sex chromosomes of the plant Silene latifolia ( Muyle et al, 2012 ) and in two Drosophila species neo-sex chromosomes that are only a few million years old ( Nozawa et al, 2014 ; Alekseyenko et al, 2013 ; Nozawa et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in male Drosophila melanogaster the entire X chromosome is expressed at roughly twice the level of autosomes to compensate for the lack of expression in the highly degenerated Y chromosome ( Conrad and Akhtar, 2012 ). In species with much younger sex chromosomes such as Drosophila miranda , dosage compensation instead occurs only at a gene-by-gene level ( Alekseyenko et al, 2013 ; Nozawa et al, 2018 ). Because the fire ant supergene is young, we hypothesize that individual genes for which the Sb allele has begun to degenerate would show evidence of dosage compensation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in D. miranda, not only XF-YP genes, but also XF-YF genes showed RLin values significantly greater than 0.5, the expected RLin value under no DC (Fig. 3A) (see also Nozawa et al 2018). In contrast, XF-YF gene upregulation was not necessarily conspicuous in D. albomicans and D. americana.…”
Section: Gene-by-gene and Global DC On Neo-xsmentioning
confidence: 73%
“…Using the RLin index (Lin et al 2012), Nozawa et al (2018) reported gene-by-gene DC on the D. miranda neo-X. Specifically, the DC level (i.e., the RLin value) for the neo-X-linked genes with pseudogenized neo-Y-linked homologs (XF-YP) was significantly greater than that for the neo-X-linked genes with functional neo-Y-linked homologs (XF-YF).…”
Section: Gene-by-gene and Global DC On Neo-xsmentioning
confidence: 99%
See 1 more Smart Citation